2003
DOI: 10.1080/gye.17.4.281.286
|View full text |Cite
|
Sign up to set email alerts
|

Treatment for ovarian hyperstimulation syndrome using an oral dopamine prodrug ,docarpamine

Abstract: Dopamine treatment constitutes a major advance towards the management of severe ovarian hyperstimulation syndrome (OHSS) by causing renal and mesenteric vasodilatation as well as diuretic and positive inotropic actions. Docarpamine, an oral dopamine prodrug, is converted into dopamine after enteral administration, and the generated dopamine causes renal vasodilatation and diuresis. The purpose of this study was to assess whether docarpamine had beneficial effects in patients with OHSS. Twenty-seven patients, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 19 publications
0
7
0
1
Order By: Relevance
“…Regarding the prevention of OHSS, the key is to identify women at risk of developing the syndrome 1 . In cases in which severe OHSS develops despite attempts to prevent it, we have reported the usefulness of an oral dopamine prodrug, docarpamine 26 , and reinfusion of ascites by means of peritoneal-venous shunting 27,28 . In the present study, a significant decrease of day-3 FSH was observed in patients with moderate or severe OHSS ( Table 3).…”
Section: Discussionmentioning
confidence: 98%
“…Regarding the prevention of OHSS, the key is to identify women at risk of developing the syndrome 1 . In cases in which severe OHSS develops despite attempts to prevent it, we have reported the usefulness of an oral dopamine prodrug, docarpamine 26 , and reinfusion of ascites by means of peritoneal-venous shunting 27,28 . In the present study, a significant decrease of day-3 FSH was observed in patients with moderate or severe OHSS ( Table 3).…”
Section: Discussionmentioning
confidence: 98%
“…Dopamine and docarpamine have also been used in patients with OHSS with positive results [51,52]. The aim of treatment is to increase renal blood flow and glomerular filtration [53].…”
Section: Medical Treatmentsmentioning
confidence: 99%
“…Improvements in urinary output and overall symptoms were reported in seven critically ill patients after they received an intravenous dopamine infusion (Ferraretti et al, 1992). Moreover, the administration of docarpamine (an oral dopamine prodrug) in 27 hospitalized patients gradually improved urinary output and ascites (Tsunoda et al, 2003). Cb2 was administered to 20 patients at risk of hyperstimulation on the evening after oocyte retrieval, and to 10 severely hyperstimulated hospitalized pregnant women (Manno et al, 2005).…”
Section: Clinical Studies For the Prevention Of Ohssmentioning
confidence: 99%